2018
DOI: 10.1101/487934
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widespread PERK-dependent repression of ER targets in response to ER stress

Abstract: The UPR (Unfolded Protein Response) is a well-orchestrated response to ER protein folding and processing overload, integrating both transcriptional and translational outputs. Its three arms in mammalian cells, the PERK translational response arm, together with the ATF6 and IRE1-XBP1-mediated transcriptional arms, have been thoroughly investigated.Using ribosome footprint profiling, we performed a deep characterization of gene expression programs involved in the early and late ER stress responses, within WT or … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…S7A,B). Previously, we have shown that the PERK-mediated repression of ER targets as part of the UPR involved eIF2⍺ phosphorylation (Gonen, 2019). We confirmed that eIF2⍺ phosphorylation occurred in both young and senescent cells upon HS, to a similar extent ( Fig.…”
Section: Loss Of Coordination Between Upr Regulatory Branches In Senesupporting
confidence: 87%
See 3 more Smart Citations
“…S7A,B). Previously, we have shown that the PERK-mediated repression of ER targets as part of the UPR involved eIF2⍺ phosphorylation (Gonen, 2019). We confirmed that eIF2⍺ phosphorylation occurred in both young and senescent cells upon HS, to a similar extent ( Fig.…”
Section: Loss Of Coordination Between Upr Regulatory Branches In Senesupporting
confidence: 87%
“…We therefore reasoned that the HS treatment in our experiment has induced the UPR. Indeed, examination of the set of mRNAs that were previously identified as the PERK-dependent translational repression UPR signature (Gonen, 2019), which was found to be highly enriched for ER targets, confirmed that this set of mRNAs was significantly repressed in both young and senescent cells in response to HS, however repression was substantially greater in senescent cells (Fig. S7A,B).…”
Section: Loss Of Coordination Between Upr Regulatory Branches In Senementioning
confidence: 55%
See 2 more Smart Citations